Mark of the demon - Rowland, Diana (New York : Bantam Books, 2009)
"Why me? Why now? That's what Beaulac, Louisiana, detective Kara Gillian was asking herself when an angelic creature named Rhyzkahl unexpectedly appeared during a routing summoning. Kara was hoping to use her occult skills to catch a serial killer, but never had she conjured anything like this unearthly beautiful and unspeakably powerful being whose very touch set off exquisite new dimensions of pleasure. But can she enlist his aid in helping her stop a killer who's already claimed the lives--and souls--of thirteen people? And should she? The Symbol Man is a nightmare that the city thought had ended three years ago. Now he's back for an encore and leaving every indication on the flesh of his victims that he, too, is well versed in demonic lore. Kara may be the only cop on Beaulac's small force able to stop the killer, but it is her first homicide case. Yet with Rhyzkahl haunting her dreams, and a handsome yet disapproving FBI agent dogging her waking footsteps, she may be in way over her head...."--p. [4] of cover.
Keywords: Serial murderers -- Fiction; Women detectives -- Fiction; Demonology -- Fiction; Louisiana -- Fiction; Fantasy fiction; Occult fiction